Renal function and use of medication preceding new-onset atrial fibrillation – results from the nationwide FinACAF study. (14th October 2021) - Jyrkila, H; Kaartinen, K; Martola, L; Halminen, O; Haukka, J; Linna, M; Mustonen, P; Putaala, J; Helin, T; Kouki, E; Luojus, A; Tiili, P; et al.
Abstract: Background and aims: Chronic kidney disease (CKD) is a global public health problem with an increasing number of patients due to obesity, hypertension, diabetes, and aging. CKD is an independent risk factor for atrial fibrillation (AF) and the incidence of AF in patients with CKD is two- to threefold higher compared to the general population. The relationship between CKD and AF is bidirectional, and the incidence of renal insufficiency is higher in patients with AF. Both AF and CKD are associated with increased risk of stroke and systemic thromboembolism, as well as an increased bleeding risk. The Finnish AntiCoagulation in Atrial Fibrillation (FinACAF) study is a nationwide study among AF patients conducted as a retrospective register-based linkage study combining data from several Finnish health care registers. We aimed to characterize demographics and medications of patients with new-onset AF included FinACAF according to stages of renal function. Method: The FinACAF study includes data from 411000 patients covering all Finnish AF patients from 1 January 2004 to 31 December 2018. Using national unique personal identification numbers, individual patients' data from ten nationwide population registries and six regional laboratory databases were linked together. The inclusion criteria of this substudy were all patients 20 years or older with a new-onset AF diagnosis between January 2010 and December 2018 and a measured estimated glomerular filtration rate (eGFR) within the proximity of the AF diagnosis. Drug purchases (date, Anatomical Therapeutic Chemical (ATC) codes, and amount) were obtained from the National Prescription Register upheld by the Social Insurance Institution of Finland. Results: 147001 patients from the initial FinACAF cohort were included in this substudy. The mean age at the time of AF diagnosis was 73 years (range 20 to 107 years), 48.9% of the patients were female. The mean age of AF patients increased in various stages of glomerular filtration at the cohort entry during 2010–2018. Baseline medications are shown in Table. The use of nonsteroidal anti-inflammatory drugs (NSAIDs) at the cohort entry decreased from 27.4% to 22.1% during 2010–2018 (p<0.001). Conclusions: Medications were used increasingly with worsening renal function, except for NSAIDs. NSAIDs use remained remarkably high in all stages of renal function, albeit much less with the lowest eGFRs. The number of patients with lipid-lowering medication was unexpectedly low considering the high cardiovascular risk in patients with impaired renal function. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): This work was supported by Aarne Koskelo Foundation, Yrjö Jahnsson Foundation, The Finnish Foundation for Cardiovascular Research, and Helsinki and Uusimaa Hospital District research fund (TYH2019309).